Philosophical Meaning of Pariangan Batik Motifs as an Effort to Preserve Minangkabau Culture - yuliarma, Yuliarma (Universitas Negeri Medan, 2023)
Batik Pariangan is a batik cloth originating from Nagari Tuo Pariangan, Tanah Datar Regency. Pariangan batik motifs come from the ancient texts of Nagari Pariangan, which in each motif has a philosophical meaning and Minangkabau cultural values. This study was conducted with the aim of describing the philosophical meaning contained in Pariangan batik motifs as an effort to preserve Minangkabau culture. This research uses a qualitative method. This method collects research data in the form of observation, interviews, documents. Data analysis is done by reducing data, presenting data and drawing conclusions. The results of this study indicate that each sample of Pariangan batik has a philosophical meaning that contains Minangkabau cultural values. These include the Nagari Pariangan motif, Bintang Batabua motif, Minangkabau Kingdom motif, Rumah Gadang motif, and Kopi Kawa motif. That every meaning it contains should be strived to continue to be learned and is still relevant to be applied in life.